A Numerical Case Study on Pier Shape Coefficient of Seismic Hydrodynamic Pressure in Design Codes. Issue 1 (February 2021) - Qin, Yifang; ZhengruTao,; Tao, Xiaxin; HaimingLiu,
Abstract: To study the pier shape coefficient of seismic hydrodynamic pressure, three waterpier coupling finite element models of piers with circular, rectangular and elliptical sections are built. The results numerically calculated with the same input ground motion show that the horizontally distributions of the hydrodynamic pressures from the vertical central lines to the edges of the three types of piers at a given depth are almost the same, the difference among the pressures on the three piers is mainly from the decreasing rate from the central line to the edge. The pressures decrease with the input direction from perpendicular to parallel. The result values of shape coefficients are close to the provisions in Japanese code, and those for circular and elliptical piers are slightly less than that stipulated in the code; and the coefficient values for rectangular pier are less than that in Euro code 8 and those for elliptical pier are in the range of the code.